Amorphous KNbO3 thin films with ferroelectric like properties - Sun, Handong (2009)
Amorphous KNbO3 films are prepared by a low-cost sol–gel method. These films show a smooth surface morphology and have good waveguiding properties. Ferroelecticlike hysteresis loops are observed in these amorphous KNbO3 films with a remanant polarization of about 6µC/cm2. After corona poling, a stable effective second harmonic generation coefficient of 0.523 pm/V is achieved.